Control and signal processing applications for mobile and aerial robotic systems - Sergiyenko, Oleg 1969-; Rivas-Lopez, Moises 1960-; Flores-Fuentes, Wendy 1978-; Rodríguez-Quiñonez, Julio C. 1985- (Advances in computational intelligence and robotics (ACIR) book series, 2020)
"This book examines the control and signal processing methods and applications in mobile and aerial robotic systems"--